Hubungan Dukungan Spiritual Dengan Kualitas Hidup Lansia Di Desa Ko’mara, Kecamatan Polongbangkeng Utara Kabupaten Takalar - Rosmin Ilham; Zainuddin (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2020)
Happy and healthy elderly people can only be achieved if they feel physical, mentally / spiritually and socially healthy, feel needed, feel loved, have self-respect, and can participate in life. Fulfillment of the highest need, namely spirituality, then a person has a quality life, thus it is appropriate for an elderly person to have their spiritual needs fulfilled. The purpose of this study was to determine the relationship between spiritual support and the quality of life of the elderly in Ko'mara Village, Polut District, Takalar Regency. This research method is descriptive-analytic with cross-sectional study design. The population in this study were all elderly who live in Ko'mara Village, Polongbangkeng Utara District, Takala Regency with a population of 333 elderly and a sample of 65 respondents, selected by random sampling. Data processing / Chi-Square Test is presented in narrative and table form. The results of this study indicate that the spiritual support of the elderly with a positive category of 36 respondents (55.4%) and a negative category of 29 respondents (44.6%), the quality of life of the elderly with a high category of 33 respondents (50.8%) and a low category of 32 respondents. (49.2%) and there is a relationship between Spiritual Support and Quality of Life of the Elderly in Ko'mara Village, Polongbangkeng Utara District, Takalar Regency. Chi-Square Test obtained value (p = 0.001). The conclusion in this study is that there is a relationship between spiritual support and the quality of life of the elderly in Ko.mara Village, Polongbangkeng Utara District, Takalar Regency. Researchers suggest the need for information by the elderly to participate in religious activities so that spiritual support can improve the quality of life of the elderly in Ko'mara Village, Polongbangkeng Utara District, Takalar Regency.